Identity without Similarity: The Relation between the Individual and Her Picture - Jerrentrup, Maja (Imaginations)

(untitled) (York University, 2019)
“This is me” we tend to say about photographs of ourselves—which is remarkable given that the image with which we identify is a two-dimensional visual taken from a very specific moment in our past. And yet the image is interpreted as an icon or an index of our present being. The problem of seeing similarity where there is difference seems to be increasing with the rise of hobby models—a niche demographic made up of mostly women between the age of 16 and 40, who enjoy posing for the camera even if they aren’t getting paid for it. This paper investigates the social and psychological motivations behind hobby modelling in the German-speaking context.